Have Institutional Investors Destabilized Emerging Markets? - Aitken, Brian (IMF Working Papers; Working Paper ;, 1996)
In the past few years there has been a large increase in portfolio capital flows into emerging markets, mostly fueled by mutual funds and other institutional investors. Based on a simple variance ratio test, this paper finds that emerging stock markets as a group experienced a sharp increase in autocorrelation in total returns at a time when institutional investors began to significantly expand their holdings in these markets. These results are consistent with the view that institutional investor sentiment toward emerging markets as an asset class can at times play a critical role in determining asset prices, with shifts in sentiment resulting in periods of bubble-like booms and busts and asset price overshooting.